Increased Incidence of Intracranial Meningiomas in Patients With Acromegaly. Issue 4 (18th October 2019) - Engelhardt, Julien; Nunes, Marie-Laure; Pouchieu, Camille; Ferrière, Amandine; San-Galli, François; Gimbert, Edouard; Vignes, Jean-Rodolphe; Laurent, François; Berge, Jérôme; Baldi, Isabelle; Tabarin, Antoine; Loiseau, Hugues
Abstract: BACKGROUND: An increased incidence of various neoplasms has been described in patients with acromegaly, and there is evidence to suggest that growth factors are risk factors for the development of meningiomas. OBJECTIVE: To study if patients with acromegaly are more at risk for developing intracranial meningiomas. METHODS: We conducted an observational study on 221 consecutive acromegalic patients recruited between January 1, 2000 and December 31, 2015, and 357 consecutive patients with a nonsomatotropic pituitary adenoma recruited between March 1, 2015 and December 31, 2016, in our institution. Patients underwent a gadolinium-enhanced 3D T1 brain magnetic resonance imaging to look for meningiomas. The proportion of meningiomas was compared between the 2 groups, and the standardized incidence ratio (SIR) was computed from the incidence rates of meningiomas observed in the population of acromegalic patients and compared to that of the general population given by the local registry of central nervous system tumors. RESULTS: Patients with acromegaly had a significant risk for developing intracranial meningiomas as compared to patients without acromegaly (7.7% vs 2.2%, P = .005, OR = 3.45 [1.46; 8.15]). There was a significant increased incidence of intracranial meningiomas in patients with acromegaly (SIR = 126 [25; 367]) as compared to the general population. CONCLUSION: Our study suggests strongly that patients with acromegaly are more at risk for developing intracranial meningiomas.